Everyday reading : poetry and popular culture in modern America - Chasar, Mike, 1970- (Columbia University Press, 2012)
"Exploring poetry scrapbooks, old-time radio show recording, advertising verse, corporate archives, and Hallmark greeting cards, among other unconventional sources, Mike Chasar casts American poetry as an everyday phenomenon consumed and created by a vast range of readers"--